Study of Pest Inventory and Disease Control in Organic-Based Food Crops at the Land Suitability Level in the Medium Plains Area in the Dry Land of North Central Timor Regency - Nikolas Nik; Aloysius Rusae; Asep Ikhsan Gumelar; Andreas Subay (Jurnal Penelitian Pendidikan IPA, 2026)
Conventional farming is a farming system still commonly used in Indonesia. Organic pesticides are pest and disease control products made from organic materials. This trend aligns with increasing public awareness of health and environmental sustainability issues. However, the success of organic farming is highly dependent on the ability of farmers to manage environmental factors, including the threat of Plant Pest Organisms (OPT), namely pests and diseases, without using chemicals. This study aims to inventory in detail the main pest and disease species in organic food crops in the middle plains of dry land TTU, analyze the correlation between the level of OPT attacks with the level of land suitability and formulate adaptive and site-specific organic control strategies, based on the inventory findings. This study was conducted in Lapeom Village, Insana Barat District, North Central Timor Regency. This study used active collection methods (browsing method) and passive (trap method). Active collection by direct collection using insect nets (sweep net) and direct collection using hands (hand picking and direct observation), while in passive collection using insect traps consisting of yellow traps, methyl eugenol attractants and pitfall traps using 5 pest control methods, namely yellow traps, methyl eugenol attractants, pitfall traps, sweep nets and hand picking and direct observation. The results of the study showed that there were 8 orders and 22 families of insect pests from 5 observation methods, namely: Pittfal trap, Yellow trap, Sweep net, Attractant and Hand picking and direct observation: Insect pests consist of: order Blattodea (family Ectobiidae), order Coleoptera (family Chrysomelidae), order Diptera (family Tepharitidae, family Muscidae, family Bibionidae, family Calliphoridae), order Hemiptera (family Cicadellidae, family Alydidae), order Lepidoptera (family Erebidae, family Crambidae), order Orthoptera (family Gryllidae, family Gryllotalpidae, family Tetrigidae, and family Tettigoniidae).